THE POTENTIALS OF ULTRASONIC ATOMIZER AUGMENTED THE SEA SALT PRODUCTIONS - I Dewa Gede Agus Tri Putra; Putu Wijaya Sunu; Nyoman Sugiartha; I Nyoman Gede Baliarta; I Wayan Temaja (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Ultrasonic atomizers can potentially augment the production of sea salt through a process known as ultrasonic nebulization. While the traditional method of sea salt production primarily relies on natural evaporation, ultrasonic atomization can accelerate the evaporation process. The process typically involves the following steps: collection of seawater, evaporation, brine crystallization and then harvesting process of the sea salt. After processing, the sea salt is typically dried and packaged for distribution and sale. In this project, influencing of ultrasonic atomizer in the process a saline water into the brine, before crystallization can be proceeded. The ultrasonic atomization process significantly increases the surface area of the seawater by converting it into fine droplets. Droplets evaporate more efficient due to large surface area of the droplets. According to testing of the research apparatus which had been conducted, an ultrasonic atomization can increase the salinity by brine evaporation or of droplet productivity of sea salt. This result had been shown that this process can be used to increasing the salinity of sea water. For further steps, this technique can potentially augment the production of sea salt.